Assessment of in vivo and in vitro antioxidant activity of methonolic extract of naringicrenulata (roxb.) Nicolson - NEELAM SINGH,; MUKESH KUMAR MEENA,; VIDYA PATNI, (International Journal of Pharma and Bio Sciences, 2017)
Free radicals are fundamental to any biochemical process and represent an essential part of aerobic life and metabolism. They are continuously produced by the body's normal use of oxygen such as respiration and some cell mediated immune functions.The aim of present research was to investigate the antioxidant potential of different plant parts of N. crenulata both in vivo and in vitro.The antioxidant activity of the methanolic extracts of in vivo and in vitro plant parts of Naringi crenulata was determined on the basis of their scavenging activity of the stable 2, 2- diphenyl-2-picryl hydrazyl (DPPH) free radical. The methanolic extracts of Naringi crenulata and Ascorbic acid (standard) showed DPPH free radical scavenging activity in a concentration range of 10-1000 μg/ml and its inhibition ranged from 21.3 -83.4 % and 49.68-94.60 % respectively. Methanolic extracts of root were found to have maximum IC50 value (898.49 µg/ml) followed by leaf (572.51 µg/ml), callus (279.49 µg/ml) and stem (147.80 µg/ml).Standard antioxidant used was Ascorbic acid (1mg/ml) having 24.79 µg/ml IC50 value. Maximum antioxidant potential was found in methanolic extract of stem while minimum was found in methanolic extract of root. This suggests that the methanolic extract of Naringi crenulata contains compounds that are capable of donating hydrogen to a free radical in order to remove odd electron which is responsible for radical’s reactivity.The high antioxidant capacity observed for methanolic extract of Naringi crenulata suggested that this plant could be used as an additive in the pharmaceutical industry providing good protection against oxidative damage.